"Szary łabędź". Kilka uwag na temat słownictwa tematycznego związanego z koronawirusem (na przykładzie "Tygodnika Powszechnego") = The Gray Swan. Some remarks on the thematic vocabulary related to the coronavirus (on the example of "Tygodnik Powszechny") - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article focuses on the vocabulary related to the coronavirus pandemic. Its main goal was to extract semantic parameters, words and word combinations in order to group them into semantic fields. Thematic fields describing the reality of Covid?19 from the perspective of human experience are presented. The highlighted vocabulary was assigned to lexical?thematic fields on the basis of the anthropocentric criterion.
Keywords: antropocentryzm; koronawirus; pola wyrazowe; semantyka; słownictwo specjalistyczne; słownictwo tematyczne; anthropocentrism; coronavirus; word fields; semantics; specialist vocabulary; thematic vocabulary